Pengaruh Kombinasi Jenis Bahan Pembawa dan Lama Masa Simpan yang Berbeda terhadap Produksi Pelet Biofungisida Trichoderma harzianum - Juni Safitri Muljowati; Purnomowati Purnomowati (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
This research aimed to know effect of carrier material combination and different storage duration on viability of T. harzianum, also to know the material type and storage duration which yielding highest conidia. Method used in this research was experimental by using Completely Randomized Design (CRD) with factorial pattern. The first factor was type of carrying material that were white sticky rice meal, mix of 75% white sticky rice meal and 25% mungbean meal, mix of 75% white sticky rice meal and 25% soybean meal, and mix of 75% white sticky rice meal and 25% skim milk that each of such material was inoculated by 108 conidia/ml of T. harzianum with storage duration levels that were 0 weeks, 3 weeks, 6 weeks, and 9 weeks. Obtained data was analyzed by analysis of variance (F test) with significantly level 95% and 99% and followed by Honestly Significant Difference (HSD). Result showed that there was interaction between types of carrying material with pellet storage period that showed significant effect on viability of T. harzianum. Carrying material type of white sticky rice meal with pellet storage period of 9 weeks resulting highest percentage acerrage of conidia seedling (viability) of T. harzianum that was 78,19%.